Analysis of Public Satisfaction Level in Public Services at Rontu Village Office, Raba District, Bima City - Hijriah Hijriah (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
The research objectives: 1) To determine the implementation of the principle of simplicity in public services for community satisfaction at the Rontu Village Head Office, Raba District, Bima City. The results of the research obtained are: 1) based on the application of the principle of simplicity in public services to increase community satisfaction at the Kelurahan Office, the results are very simple and are in accordance with the Regulation of the Minister of Administrative Reform Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Delivery Units. 2) Based on the application of the principle of accuracy in public services to increase community satisfaction at the Rontu Village Office, the results are very accurate and are in accordance with the Minister of Administrative Reform Regulation Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Delivery Units. 3) Based on the application of the principle of completeness of facilities and infrastructure in public services to increase community satisfaction at the Rontu Village Office, the results are very complete and are in accordance with the Minister of Administrative Reform Regulation Number 14 of 2017 concerning Guidelines for Preparing Community Satisfaction Surveys for Public Service Delivery Units.